2018
DOI: 10.1039/c8ra04222e
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electrochemical properties and stress corrosion cracking of super 13Cr under an HTHP CO2 environment

Abstract: The degradation of a surface film induces pitting corrosion, which further increases SCC susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Observation of Cr(OH)3 has been reported by Yue et al [16], who worked with super 13Cr in CO2-saturated water at temperature ranges of 120°C and 150°C. We reported that the amorphous Cr(OH)3 can be detected by using XPS at the surface, agreeing with the observations here.…”
Section: Effects Of Temperature and Immersion Time On Thermodynamicsmentioning
confidence: 67%
See 1 more Smart Citation
“…Observation of Cr(OH)3 has been reported by Yue et al [16], who worked with super 13Cr in CO2-saturated water at temperature ranges of 120°C and 150°C. We reported that the amorphous Cr(OH)3 can be detected by using XPS at the surface, agreeing with the observations here.…”
Section: Effects Of Temperature and Immersion Time On Thermodynamicsmentioning
confidence: 67%
“…From previous research, it has been found that the thickness of the film reaches the micronscale at 150 o C on super 13Cr surfaces after 30 days exposure [16], in comparison to the film formed at temperatures of 120°C or below which is orders of magnitude thinner. Zhang et al [9] proposed that the surface films may comprise both Cr2O3 and FeCO3 at 150 °C.…”
Section: Introductionmentioning
confidence: 95%
“…where R ct(inh) and R ct are charge transfer resistance in the absence and presence of inhibitors, respectively. The result of EIS indicated that the radius of capacitance arc is related to the charge transfer resistance and double electric layer capacitor produced in the process of corrosion [18][19][20]. As figure 5 shows, there is a capacitive arc in the presence and absence of PPAPO with Na 2 WO 4 at 333 K, and the change of capacitance arc radius will occur with the concentration of PPAPO.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…While many ultra-depth well tubes fractured due to stress corrosion cracking (SCC), further research interests should be shifted to SCC in the HTHP environment (Zhu et al, 2011;Lei et al, 2015;Zhang et al, 2019). The SCC susceptibility of HP-13Cr SS was up to 42% exposure at 150°C and 1 MPa CO 2 environment (Yue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%